2016
DOI: 10.3389/fmicb.2015.01540
|View full text |Cite
|
Sign up to set email alerts
|

Recombination Does Not Hinder Formation or Detection of Ecological Species of Synechococcus Inhabiting a Hot Spring Cyanobacterial Mat

Abstract: Recent studies of bacterial speciation have claimed to support the biological species concept—that reduced recombination is required for bacterial populations to diverge into species. This conclusion has been reached from the discovery that ecologically distinct clades show lower rates of recombination than that which occurs among closest relatives. However, these previous studies did not attempt to determine whether the more-rapidly recombining close relatives within the clades studied may also have diversifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 87 publications
(206 reference statements)
2
22
1
Order By: Relevance
“…They concluded that the higher rates of recombination within the clades prevented ecological diversification. However, these studies did not actually attempt to determine whether the more rapidly recombining close relatives within the clades may have diversified ecologically, without the benefit of sexual isolation (44). My colleagues and I recently investigated, in hot spring Synechococcus, the possibility of ecological diversification among extremely close relatives that were not sexually isolated, and we found that the highest rates of recombination within clades did not prevent their ecological diversification (44).…”
Section: The Dynamic Properties Of Speciesmentioning
confidence: 98%
See 1 more Smart Citation
“…They concluded that the higher rates of recombination within the clades prevented ecological diversification. However, these studies did not actually attempt to determine whether the more rapidly recombining close relatives within the clades may have diversified ecologically, without the benefit of sexual isolation (44). My colleagues and I recently investigated, in hot spring Synechococcus, the possibility of ecological diversification among extremely close relatives that were not sexually isolated, and we found that the highest rates of recombination within clades did not prevent their ecological diversification (44).…”
Section: The Dynamic Properties Of Speciesmentioning
confidence: 98%
“…However, these studies did not actually attempt to determine whether the more rapidly recombining close relatives within the clades may have diversified ecologically, without the benefit of sexual isolation (44). My colleagues and I recently investigated, in hot spring Synechococcus, the possibility of ecological diversification among extremely close relatives that were not sexually isolated, and we found that the highest rates of recombination within clades did not prevent their ecological diversification (44). Where it has been investigated in bacteria, an absence of sexual isolation has not precluded ecological diversification among closest relatives (45).…”
Section: The Dynamic Properties Of Speciesmentioning
confidence: 99%
“…One view is that genetic exchange rarely hinders genetic divergence in bacterial populations (56). Rather, recombination fosters the acquisition of novel genes and operons that aid in adaptation, thereby promoting divergence (5,57). A competing hypothesis suggests that recombination is a cohesive force that prevents bacterial diversification and maintains lineages by homogenizing populations (57,58).…”
Section: Figmentioning
confidence: 99%
“…H omologous and nonhomologous recombination are major drivers of evolution in bacterial populations (1)(2)(3)(4)(5). Horizontal gene transfer (HGT; also called nonhomologous recombination or lateral gene transfer) occurs between and within species (6).…”
mentioning
confidence: 99%
“…It is also consistent with observed reductions of HR between ecologically distinct species (Polz et al ). Melendrez et al () also found that gene‐specific selective sweeps occur within ecologically divergent species of Synechococcus , but in rebuttal of this hypothesis, they argued that separate gene pools were a consequence of ecological divergence rather than a cause. In theory, strong enough selection against recombinant genotypes could permit divergence even without niche‐specific gene flow at the outset (Bürger, ; Gavrilets, ).…”
Section: Introductionmentioning
confidence: 99%